2016
DOI: 10.1111/evj.12565
|View full text |Cite
|
Sign up to set email alerts
|

Does oral prednisolone treatment increase the incidence of acute laminitis?

Abstract: Administration of oral prednisolone did not increase the risk of laminitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 32 publications
(67 reference statements)
3
33
0
1
Order By: Relevance
“…Numerous episodes of corticosteroid use without adverse effects are clearly documented in recent publications (Jordan et al . ; Potter et al . ; Welsh et al .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous episodes of corticosteroid use without adverse effects are clearly documented in recent publications (Jordan et al . ; Potter et al . ; Welsh et al .…”
Section: Discussionmentioning
confidence: 99%
“…Laminitis is also often linked with pasture consumption and is reported to occur in association with iatrogenic glucocorticoid administration . However, recent research included in this online collection suggests that the dose, duration and type of corticosteroid used influences whether laminitis risk increases with administration . This retrospective analyses of clinical records found that oral prednisolone treatment, a common prescription in equine medicine, was not associated with an increased incidence of laminitis.…”
mentioning
confidence: 86%
“…No relationship was found in a previous retrospective study of horses on long‐term therapy with prednisolone and the occurrence of laminitis (Jordan et al . ).…”
Section: Gastrointestinal Systemmentioning
confidence: 97%